2014
DOI: 10.1051/0004-6361/201321836
|View full text |Cite
|
Sign up to set email alerts
|

An exploration of Pluto’s environment through stellar occultations

Abstract: Context. Pluto has five known satellites with diameters ranging from ∼1200 km down to ∼40 km, a possible outcome of a collisional origin. Smaller objects probably exist and may maintain tenuous rings, thus representing hazards during the New Horizons flyby of July 2015. Aims. The goal is to provide an upper limit for the numbers of unseen small bodies and/or equivalent widths of putative Pluto rings. Methods. We use a Pluto stellar appulse on April 10, 2006, and a stellar occultation by the dwarf planet on Jun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 35 publications
0
16
0
Order By: Relevance
“…One of the motivations of the present work has to do with the possibility of grasping the basic features of the wavefields scattered from "large" tridimensional objects in terms of paraxial diffraction from equivalent planar apertures, a topic that continues to receive attention, even in recent times [40], also in light of its intriguing astronomical applications [41]. In particular, we believe that the approach outlined here could be helpful in the study of diffraction effects observed during celestial occultation experiments [42][43][44][45][46].…”
Section: Discussionmentioning
confidence: 99%
“…One of the motivations of the present work has to do with the possibility of grasping the basic features of the wavefields scattered from "large" tridimensional objects in terms of paraxial diffraction from equivalent planar apertures, a topic that continues to receive attention, even in recent times [40], also in light of its intriguing astronomical applications [41]. In particular, we believe that the approach outlined here could be helpful in the study of diffraction effects observed during celestial occultation experiments [42][43][44][45][46].…”
Section: Discussionmentioning
confidence: 99%
“…They placed a 3σ upper limit on the azimuthally averaged normal I/F of ring particles of 5.1 × 10 7 at a distance of 42 000 km from the Pluto-Charon barycentre. Boissel et al (2014) derive an upper limit of 15 000 for the number of bodies smaller than 0.3 km at distances smaller than 70 000 km from Pluto's system barycentre. The impactor velocity of colliding bodies ranges from 10−100 m s −1 (Steffl & Stern 2007).…”
Section: Introductionmentioning
confidence: 91%
“…The ring systems of both Uranus and Neptune were detected by stellar occultations before they were imaged (Guinan et al 1982;Elliot et al 1977), and occultations were recently used to detect a ring system surrounding the asteroid Chariklo (Braga-Ribas et al 2014). In the Saturn system, ring occultations are frequently observed with Cassini to study structure at scales much smaller than the imaging resolution limit.…”
Section: Stellar Occultations Of Ringsmentioning
confidence: 99%
“…Searches for rings here or elsewhere in the system have so far detected nothing (Boissel et al 2014;McKay 2008;Steffl and Stern 2007;Pasachoff et al 2006). In this paper, we present results which improve the upper limit on the putative Plutonian rings.…”
Section: Stellar Occultations Of Ringsmentioning
confidence: 99%
See 1 more Smart Citation